Proposal to optimize electricity consumption costs for regulated clients in medium and low voltage - case study: Peru - Jorge Ramos, Jhanira Felicita (2021)
This article presents the results of the savings for electricity consumption obtained from the analysis and application of the tariff options for regulated customers in medium and low voltage in the Peruvian market. The methodology considers the evaluation of 152 consumption profiles of various clients in the commercial and industrial sector, with which simulation sheets were designed for the construction of the load diagrams in order to know the production cycles of the companies. Based on the load diagram and the concepts contemplated in each electricity tariff, the billing scenarios were simulated in the different existing options in order to choose the most convenient tariff for the analyzed company, finding economic reductions up to 23% for the energy payment electrical power as shown in the present study. Finally, a summary table of the rate options associated with the different companies according to their business activity is presented, which will serve as a guide for owners and / or administrators when choosing a rate option.